Pedagogical Innovation and English language Proficiency: A comparative analysis of activity-based learning in urban and rural schools in Karnataka (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Introduction: English in India represents the historical period of Indian colonization and our lingering influence from the British rule.Aim of the study: The primary objective of the research is to Pedagogical Innovation and English Language Proficiency: A Comparative Analysis of Activity-Based Learning in Urban and Rural Schools in Karnataka.Material and method: This study examines the relationship between English language proficiency and various factors, including rural perspectives on the English language, the impact of religious beliefs, the culture of rural schools, the methods of instruction, and the motivations underlying peer pressure, which are collectively referred to as rural cultural factors.Conclusion: Upon examining the study, it becomes evident that all the issues indicated by the respondents are intricately linked to the rural setting.